Empowering parental choices: exploring barriers and enablers to healthy eating among parents - a scoping review - Waisulqrnai, Siti Adibah; Ibrahim, Muhamad Ariff; Hamirudin, Aliza Haslinda; Jaafar, Nurul Hazirah; Saad, Nurulwahida (UPM Press, 2024)
Establishing healthful childhood dietary habits profoundly influences lifelong well-being, with parental roles being pivotal. This scoping review aims to identify barriers and enablers to healthy eating among parents. A search of academic journals from 2004 to 2023 used search terms addressing barriers to healthy eating, enablers to healthy eating, and caregivers or parents in the four databases. They are yielding nine studies for inclusion. Findings reveal time, cost, familial, societal influence, and taste and preferences as barriers, while enablers include parental control, education on a healthy diet, and positive role models. This review presents a comprehensive view of the factors that affect parent’s decisions regarding their children’s healthy eating. However, further research is necessary to adapt to the rapidly changing lifestyles and develop interventions that help parents make informed and healthy choices for their children in the current context.